2014
DOI: 10.1016/j.procir.2014.03.194
|View full text |Cite
|
Sign up to set email alerts
|

Towards Early Estimation of Part Accuracy in Additive Manufacturing

Abstract: Additive manufacturing (AM) is becoming more diffused. In spite of its advantages: capability to manufacture complex internal feature and material efficiency, AM has inherent drawback from its layer-by-layer nature. "Staircase effect" is observed due to the slicing process of the computer model in which a rough surface from a theoretically smooth surface will be obtained. Hence, there will be a deviation of the produced part from its nominal model. A methodology to predict the deviation of computer model of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The aim of an optimal build orientation selection is to improve surface finish, increase part strength in a specific direction, reduce support material, minimize build time and maximize the geometric accuracy [54]. However, there are several factors that must be considered when selecting the build orientation in FDM systems [9, 51, 55-57]:…”
Section: Build Orientationmentioning
confidence: 99%
“…The aim of an optimal build orientation selection is to improve surface finish, increase part strength in a specific direction, reduce support material, minimize build time and maximize the geometric accuracy [54]. However, there are several factors that must be considered when selecting the build orientation in FDM systems [9, 51, 55-57]:…”
Section: Build Orientationmentioning
confidence: 99%
“…MIP-SLA-built cylinders and cubes were used for checking the deviation models, while this model-build method was not comprehensive enough to cover all defect forms with obvious effects. Moroni et al (2014) proposed a methodology to estimate dimensional and geometric deviation of AM part features by analyzing the STereoLithography (STL) input file. This work mainly considered the incorporating confounding errors caused by the "stair-step" effect and shrinkage of FDM process.…”
Section: Additive Manufacturing Geometrical Quality Analysis and Estimentioning
confidence: 99%
“…Typically, the CAD model is converted to a stereolithography (*.stl) file format where the designed geometries and surfaces are discretised into geometric meshes. A macro-level 'stair-case' effect can occur on part surfaces due this discretisation (Moroni et al, 2014). In addition it has been shown that melt pool dynamics have a large influence on sidewall dimensions for the finished parts (Lee and Farson, 2015).…”
Section: Geometrical Anomaliesmentioning
confidence: 99%